ED‐DEL: Development of a change package and toolkit for delirium in the emergency department. Issue 2 (29th April 2021) - Kennedy, Maura; Webb, Margaret; Gartaganis, Sarah; Hwang, Ula; Biese, Kevin; Stuck, Amy; Lesser, Adriane; Hshieh, Tammy; Inouye, Sharon K.
Abstract: Delirium is a common and deadly problem in the emergency department affecting up to 30% of older adult patients. The 2013 Geriatric Emergency Department guidelines were developed to address the unique needs of the growing older population and identified delirium as a high priority area. The emergency department (ED) environment presents unique challenges for the identification and management of delirium, including patient crowding, time pressures, competing priorities, variable patient acuity, and limitations in available patient information. Accordingly, protocols developed for inpatient units may not be appropriate for use in the ED setting. We created a Delirium Change Package and Toolkit in the Emergency Department (ED‐DEL) to provide protocols and guidance for implementing a delirium program in the ED setting. This article describes the multistep process by which the ED‐DEL program was created and the key components of the program. Our ultimate goal is to create a resource that can be disseminated widely and used to improve delirium identification, prevention, and management in older adults in the ED.